The effect of rate changes of the constant external magnetic field on the coefficient of ultrasonic wave absorption in polydispersive magnetic fluid - JÓZEFCZAK, A.; SKUMIEL, A.; ŁABOWSKI, M. (Archives of Acoustics, 2000)
In this paper are presented experimental results of changes of the ultrasonic wave absorption coefficient as the function of external magnetic field intensity, for different rates of magnetic field changes in a polydispersive magnetic liquid EMG-605 based on water. Measurements were performed for two frequencies of ultrasonic wave: 3.6 MHz and 6.12 MHz, where the directions of propagation of ultrasonic wave and external magnetic field were mutually parallel and perpendicular. This paper presents also the radii of detected spherical clusters formed in magnetic fluid under the influence of magnetic field.